Effect of BMP-2 Delivery Mode on Osteogenic Differentiation of Stem Cells. (19th January 2017) - Jung, Taekhee; Lee, John Hwan; Park, Soonjung; Kim, Yong-Jin; Seo, Joseph; Shim, Hye-Eun; Kim, Ki-Suk; Jang, Hyon-Seok; Chung, Hyung-Min; Oh, Seong-Geun; Moon, Sung-Hwan; Kang, Sun-Woong
Abstract : Differentiation of stem cells is an important strategy for regeneration of defective tissue in stem cell therapy. Bone morphogenetic protein-2 (BMP-2) is a well-known osteogenic differentiation factor that stimulates stem cell signaling pathways by activating transmembrane type I and type II receptors. However, BMPs have a very short half-life and may rapidly lose their bioactivity. Thus, a BMP delivery system is required to take advantage of an osteoinductive effect for osteogenic differentiation. Previously, BMP delivery has been designed and evaluated for osteogenic differentiation, focusing on carriers and sustained release system for delivery of BMPs. The effect of the delivery mode in cell culture plate on osteogenic differentiation potential was not evaluated. Herein, to investigate the effect of delivery mode on osteogenic differentiation of BM-MSCs in this study, we fabricated bottom-up release and top-down release systems for culture plate delivery of BMP-2. And also, we selected Arg-Gly-Asp- (RGD-) conjugated alginate hydrogel for BMP-2 delivery because alginate is able to release BMP-2 in a sustained manner and it is a biocompatible material. After 7 days of culture, the bottom-up release system in culture plate significantly stimulated alkaline phosphate activity of human bone marrow-mesenchymal stem cells. The present study highlights the potential value of the tool in stem cell therapy.